2007
DOI: 10.1007/s00253-006-0757-z
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus methanolicus: a candidate for industrial production of amino acids from methanol at 50°C

Abstract: Amino acids are among the major products in biotechnology in both volume and value, and the global market is growing. Microbial fermentation is the dominant method used for industrial production, and today the most important microorganisms used are Corynebacteria utilizing sugars. For low-prize bulk amino acids, the possibility of using alternative substrates such as methanol has gained considerable interest. In this mini review, we highlight the unique genetics and favorable physiological traits of thermotole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
63
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

5
5

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 50 publications
1
63
0
2
Order By: Relevance
“…We have previously demonstrated that wild-type B. methanolicus produces 58 g/liter of L-glutamate (6), while mutants generated by random chemical mutagenesis have been reported to produce up to 37 g/liter of L-lysine (16,23,34). Favorable properties of B. methanolicus, such as a lack of sporulation at high temperatures, utilization of methanol as an energy and carbon source, a high methanol conversion rate, a high theoretical yield of L-lysine, and an optimal growth temperature of 50°C, indicate that this organism may represent a possible future noncarbohydrate substrate alternative for large-scale production of L-lysine (5).…”
mentioning
confidence: 99%
“…We have previously demonstrated that wild-type B. methanolicus produces 58 g/liter of L-glutamate (6), while mutants generated by random chemical mutagenesis have been reported to produce up to 37 g/liter of L-lysine (16,23,34). Favorable properties of B. methanolicus, such as a lack of sporulation at high temperatures, utilization of methanol as an energy and carbon source, a high methanol conversion rate, a high theoretical yield of L-lysine, and an optimal growth temperature of 50°C, indicate that this organism may represent a possible future noncarbohydrate substrate alternative for large-scale production of L-lysine (5).…”
mentioning
confidence: 99%
“…Methanol has several unique properties that make it an interesting alternative to molasses for such uses (5,36). So far, mainly three different methylotrophic bacteria have been explored to various levels for such purposes: the Gram-negative and obligate methylotrophs Methylophilus methylotrophus and Methylobacillus glycogenes and the Grampositive, thermotolerant, and restricted methylotroph Bacillus methanolicus (5,7).…”
mentioning
confidence: 99%
“…1). Regeneration of Ru5-P involves enzymes shared with glycolysis and the pentose phosphate pathway (9) (Fig. 1).…”
mentioning
confidence: 99%